2022
DOI: 10.1002/vms3.837
|View full text |Cite
|
Sign up to set email alerts
|

CT anatomy of cervical vertebrae of Asian elephant (Elephas maximus)

Abstract: Background Elephants are currently the largest mammals on earth. A comprehensive examination of the anatomy of this animal to diagnose various disorders is required. In addition, due to the heavy head of these animals, adaptations have been made in the anatomical structure of the neck that is worth studying. Objective This study aimed to investigate a standard morphologic and morphometric description of the elephant cervical spine. Another aim of this study was to compare the changes in the cervical skeleton o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Anatomical descriptions of elephants are often based on standard anatomical and histological techniques, focusing on microanatomy and biomechanics together with musculoskeletal anatomy [19][20][21]. Computer tomography is also used for studying the skeleton and bones, including the fine structure of the bones [22]. A combination of these, with more advanced technologies such as X-ray fluorescence [23], radiography, MRI, and immunohistochemistry, was introduced in studies which demonstrated the detailed anatomy of the stifle [14] and the brain [13].…”
Section: Introductionmentioning
confidence: 99%
“…Anatomical descriptions of elephants are often based on standard anatomical and histological techniques, focusing on microanatomy and biomechanics together with musculoskeletal anatomy [19][20][21]. Computer tomography is also used for studying the skeleton and bones, including the fine structure of the bones [22]. A combination of these, with more advanced technologies such as X-ray fluorescence [23], radiography, MRI, and immunohistochemistry, was introduced in studies which demonstrated the detailed anatomy of the stifle [14] and the brain [13].…”
Section: Introductionmentioning
confidence: 99%
“…The most prominent advantage of these techniques is that anatomical structures can be investigated in live animals. Diagnostic imaging techniques are very suitable for anatomical studies of the coelomic cavity organs of animals such as turtles that are difficult to access, and methods such as CT scans have been used for these studies (Zehtabvar et al, 2014(Zehtabvar et al, , 2015(Zehtabvar et al, , 2022a(Zehtabvar et al, , 2022b. In addition, other methods such as ultrasonography have been used to study the anatomy of the heart structure in sturgeons (Zehtabvar et al, 2018(Zehtabvar et al, , 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Among these methods, CT scan is a precise method for topographic and morphometric studies, especially about the structures of the respiratory system. One of the most important features of using these techniques in anatomy studies is that there is no need to euthanise the studied animal (Zehtabvar et al, 2022a(Zehtabvar et al, , 2022b.…”
Section: Introductionmentioning
confidence: 99%